The “wound” metaphor in the border narratives of Ana Castillo and Graciela Limón - Farid, Sonia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
This paper explores the manifestations of the wound metaphor in two Mexican-American border novels: The Guardians (2007) by Ana Castillo and The River Flows North by Graciela Limón (2009). This will be done by analyzing the metaphor as tackled by Anzaldúa and Fuentes then examining the detrimental impact of the border on characters that are affected by it in one way or another whether through attempting to cross to the United States, crossing back to Mexico, or living in border towns.